Tectonically-controlled disaster risk assessment study along Palu-Koro Fault in Donggala Regency, Central Sulawesi: Record from 2018 earthquake effect - Sumarlin Usman; Asri Jaya HS; Adi Maulana (Universitas Muslim Indonesia, 2022)
One of the major tectonic manifestation in Sulawesi Island is the Palu-Koro fault which extends north-northwest to south-eastwards in the centre of the island. The presence of the Palu-Koro Fault has responsible for the series of natural disasters occurred in Central part of Sulawesi and its surrounding which include earthquake, tsunami, liquefaction and subsidence. The need for further tectonic studies and geological structure mapping surrounding the fault is very important for disaster risk reduction strategy including mitigation effort to reduce casualties affected by future disasters. The study was conducted along Palu-Koro Fault Zone in Donggala Regency, Central Sulawesi. This study aims to assess the disaster risk including vulnerability, threat and capacity that generated by tectonically-controlled process along Palu-Koro Fault in Donggala Regency due to 2018 earthquake. The methodology used includes disaster risk reduction assessment approach, field geological structure observation, satellite imagery analysis using high-resolution satellite image from the Center for Remote Sensing Technology and LAPAN (National Institute of Aeronautics and Space), Pleiades satellite imagery with a resolution of 0.5 meters and SPOT 7 satellite imagery with a resolution of 1.5 meters. The result shows that the study area is prone to tsunami, earthquake, liquefaction and subsidence processes. Tsunami, earthquake and subsidence are grouped into high-risk disaster whereas liquefaction is considered as having moderate-risk level. The results of the assessment are expected to be used as a solid basis for planning disaster risk reduction efforts in the future.